PENERAPAN KEADAAN MERINGANKAN TERHADAP TINDAK PIDANA KORUPSI SUAP DALAM JABATAN - Maria Rosari Putri, (2023)
In giving consideration to a decision, the judge must pay attention to the aggravating or mitigating circumstances of the defendant as stipulated in Article 197 of the Criminal Procedure Code (KUHAP). Similarly, in Article 8 paragraph (2) of the Judicial Power Law, it is stated that judges must also consider the good and bad nature of the defendant. However, the aggravating and mitigating circumstances do not yet have clear benchmarks or guidelines. The application of mitigating circumstances by judges and the reduction of criminal sanctions are often considered inappropriate. In this study, the author raises the case of the application of mitigating circumstances to Edhy Prabowo, the Minister of Marine Affairs and Fisheries, who committed the corruption crimes of bribery in position of power. This research was conducted to examine and analyze the relevance of the application of mitigating circumstances in cases of bribery in position of power in relation to the principles of good governance and the application of the good and bad nature of the defendant in the judge's consideration. This research uses statutory approach, concept approach and case approach. The results of this study explain that the application of mitigating circumstances in case of bribery in position of power clearly violates the general principles of good governance. Especially for an official, as explained in Article 52 of the Criminal Code, which can be one of the indicators in applying aggravating circumstances to defendant who is state official. Therefore, the consideration of mitigating circumstances in cases of bribery in position of power must be based on legal facts revealed comprehensively in the trial to provide justice, usefulness, and certainty for all parties. On the other hand, a rule is needed as a guide for judges in implementing mitigating circumstances against officials who accept bribes in their positions, so that they have clear benchmarks and can prevent acts of abuse of power by taking cover behind the word "judge independence".